Microsoft Word 2000. Advanced course - Napier, H. Albert (South-Western Educational Pub, 2000)
With a completion time of 75+ hours, this book features extensive step-by-step instructions combined with numerous screen illustrations to enable people to learn the more advanced features of Microsoft Word 2000